Low-dose chemotherapy impact on metastatic breast cancer : a pre-clinical study - Kumar, Dileep (2024)
Tese (doutorado) — Universidade de Brasília, Instituto de Ciências Biológicas, Programa de Pós-Graduação em Biologia Animal, 2024.